Properties of Slow Magnetoacoustic Waves Observed Simultaneously Using Hi-C 2.1 and AIA - Suraj K. Tripathy; S. Krishna Prasad; D. Banerjee (The Astrophysical Journal, 2025)
Propagating slow magnetoacoustic waves are commonly observed in different coronal structures but are most prominent in active region fan loops. Their rapid damping with damping lengths of the order of a wavelength has been investigated in the past by several authors. Although different physical mechanisms have been proposed, significant discrepancies between the theory and observations remain. Recent high-resolution observations captured simultaneously by two different instruments reveal distinct damping lengths for slow magnetoacoustic waves, although their passbands are similar. These results suggest a possible contribution of instrumental characteristics to the measurement of damping lengths. Here, we analyze the behavior of slow waves using a different pair of instruments in order to check the prevalence of such results. In particular, the cotemporal observations of active region NOAA AR 12712 by the High-resolution Coronal Imager (Hi-C 2.1; Hi-C) and the Atmospheric Imaging Assembly (AIA) on board the Solar Dynamics Observatory (SDO) are utilised. The estimated oscillation periods of slow magnetoacoustic waves identified from these data are 2.7 ± 0.2 minutes from SDO/AIA and 2.8 ± 1.2 minutes from Hi-C 2.1. The corresponding propagation speeds are found to be 46.0 ± 1.7 and 48.1 ± 0.6 km s ^−1 , respectively. Damping lengths were calculated by two different methods, the phase tracking method (PTM) and the Amplitude Tracking Method (ATM). The obtained values from the PTM are 4.0 ± 2.1 and 4.1 ± 0.3 Mm, while those from the ATM are 3.4 ± 1.0 and 3.7 ± 0.1 Mm, respectively, for the AIA and Hi-C data. Our results do not indicate any notable difference in damping lengths between these instruments.